Korelasi Morfometrik Cangkang Terhadap Berat Daging Kerang Darah (Anadara Granosa) Di Tambak Dan Habitat Alami Sumatera Utara - Salsabila Andini Putri; Syarifuddin (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This study focuses on the morphometric relationship of cultured blood cockles (Anadara granosa) and compares it with the morphometrics of cockles from natural habitats. Sampling was carried out at three stations in 2 different habitats, with a total of 90 individuals taken. The method used was a survey study with the research objects being blood cockles, substrate, and salinity. The variables observed in this study were the morphometrics of shell length, shell width, shell height, shell thickness, total weight, shell weight, and meat weight in ponds and natural habitats. The results of this study indicate that blood cockles that live in the wild have a higher size than those in ponds. Environmental conditions in ponds and natural habitats are still within normal limits of 24-30‰. The composition of the cultivated pond substrate is muddy (51%), while the natural habitat is sandy (51%).